Equatorial carbonates: an earth systems approach - Wilson, Moyra (Blackwell Publishing Ltd, 2012)
The hypothesis here is that an earth systems ‘processes to products’ approach can be used to better develop predictive models for the recognition and assessment of under-evaluated equatorial carbonate systems. Warm temperatures, together with common clastic, fresh water and nutrient influx, as well as basinal settings in the equatorial tropics, all have a major impact on carbonate deposition and diagenesis. Specific features of equatorial carbonate systems resulting from the combination of processes acting in the region include: common occurrence of photoautotrophs and heterotrophs, aragonitic and/or calcitic dominant mineralogies, lack of coated grains or aggregates, common associations with clastics, lack of associations with evaporites, and diversity of platform types, including oligophotic ones. Additional diagenetic characteristics include: common micritization and bioerosion, paucity of marine cements, extensive vadose dissolution and concomitant phreatic cementation. There is also significant replacement of aragonite by calcite in regions of meteoric groundwater flow, common burial compaction and leaching, as well as localized massive dolomitization via sea water or continental derived groundwater flow. Although equatorial carbonates fall into the warm-water Photozoan Association, many of the features described above are at odds with models derived from their warm-water, arid-zone counterparts. Instead, a range of the equatorial carbonate features show some similarities with those formed in cool waters, and there have been difficulties separating carbonates from these two very different climatic regimes. Recommendations for the recognition of Phanerozoic regional equatorial carbonate development are: (i) a diversity of calcitic and/or aragonitic photoautotrophs; plus (ii) common elements of the Heterozoan Association; plus (iii) independent (for example, isotopic) evidence for warm temperatures (>22°C). Additional indicators towards a humid equatorial setting are: (iv) situation in appropriate palaeolatitudes; (v) lack of association with sedimentary evaporites, coated grain or aggregates; and (vi) geochemical evidence for reduced marine salinity and/or nutrient upwelling. The aim is that this work will lead to greater awareness and understanding of equatorial carbonate systems, and contribute to the development of globally predictive models to better understand past and likely future environmental change.